STUDI ANALISIS UFR (UNDER FREQUENCY RELAY) PADA GARDU INDUK PESANGGARAN - Bhrama Sakti K.P.; A.A. Gede Maharta Pemayun; I Gede Dyana Arjana (Program Studi Teknik Elektro UNUD, 2019)
The disruption of the electric power system due to overcurrent causes a trip to the 3rd generator of pesanggaran power plant . This causes a decrease in frequency due to the system losing its supply. Frequency interference can be detected automatically with UFR (Under Frequency Relay). The working principle of UFR is to compare the value of the system frequency and the value of the frequency setting. The comparison will determine how much load is released to balance the generator supply. This study analyzes UFR performance at Pesanggaran Substation by simulating a case of the generator being released so as to produce a decreased system frequency state. The method used is by comparing the ETAP simulation results and calculation results. The results of the comparison obtained the system recovery time when the conditions (gen1 tripped), (gen1 and gen2 tripped), and (gen1, gen2, and gen3 tripped), each is 1.171s; 4,531s; and 4,514s.